Participatory Learning and Action for Nutrition Sensitive Farming System among Tribal families. - Joshi, Jayesh. (Tufts University. Tisch Library., 2017)
Jayesh's presentation explores a PLA (Particaptory Learning and Action) tool and its evolution in promoting Nutrition Sentitive Farming Systems.